2019
DOI: 10.4081/ejtm.2019.8372
|View full text |Cite
|
Sign up to set email alerts
|

A global approach for plantar fasciitis with extracorporeal shockwaves treatment

Abstract: Extracorporeal Shockwaves Treatment is considered an effective therapeutic option for plantar fasciitis, but the standard application in the medial insertion of the plantar fascia on the calcaneus has provided ambiguous evidences. In this case, a 63-year man with plantar fasciitis was treated in a 3-session program and Foot and Ankle Outcome Scale and Foot Functional Index questionnaires were chosen for the clinical outcome evaluation. The therapy was focused on the active trigger or myofascial points of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…The type of collagen fibers present in the deep fasciae can change depending on various hormonal, mechanical and chemical inputs. Considered an effective therapeutic option for plantar fasciitis and myofascial disorders [ 64 ], extracorporeal shockwave treatment enhances fibroblast proliferation and differentiation by activating gene expression for transforming growth factor β1 and collagen types I and III [ 65 ]. Pavan et al [ 66 ] demonstrated that aging increases the amount of type I collagen fibers in the extracellular matrix (ECM) of the epimysial fascia, and thus increase its stiffness.…”
Section: The Extracellular Matrix: the Fibrous Componentmentioning
confidence: 99%
“…The type of collagen fibers present in the deep fasciae can change depending on various hormonal, mechanical and chemical inputs. Considered an effective therapeutic option for plantar fasciitis and myofascial disorders [ 64 ], extracorporeal shockwave treatment enhances fibroblast proliferation and differentiation by activating gene expression for transforming growth factor β1 and collagen types I and III [ 65 ]. Pavan et al [ 66 ] demonstrated that aging increases the amount of type I collagen fibers in the extracellular matrix (ECM) of the epimysial fascia, and thus increase its stiffness.…”
Section: The Extracellular Matrix: the Fibrous Componentmentioning
confidence: 99%
“…The evaluations of the aforementioned study were made at the baseline and at the end of the treatment, and there was a relatively short follow‐up period. In this study, the fact that ESWT plus low‐dye KT treatment achieved more effective outcomes than ESWT at 4 weeks after the treatment ended shows the effectiveness of low‐dye KT application when added to the ESWT treatment, which is an accepted therapy 19‐22 . Frassanito et al 23 applied ESWT plus KT to one group and ESWT to the other group by dividing patients with calcific tendinopathy in the shoulder.…”
Section: Discussionmentioning
confidence: 72%
“…angiogenesis-related markers. 22,25 ESWT therapy was approved by the American Food and Drug Administration in 2000 to treat PF. 24 In this study, in accordance with the literature, a decrease in pain and improvement in foot function scale were observed in all groups after ESWT.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
“…Alrededor de un 90 % de los pacientes son tratados con tratamientos conservadores como primera opción 8 . Los tratamientos conservadores más comunes son: reposo, ejercicios, estiramientos o medicación antinflamatoria 3,8 . Si en un plazo de unos 6 meses los síntomas no mejoran, entonces se propondría la intervención quirúrgica 4 .…”
Section: Introductionunclassified